Reengineering towards components using "Reconn-exion". - Le Gear, Andrew (Software engineering notes.)
Continuing to develop software from scratch will not be feasible indefinitely. Reusing existing software would seem to be a viable solution to this problem. The paradigm of component-based development (CBD) explicitly accounts for reuse in its process. Unfortunately the majority of existing software systems are not implemented using CBD, thus reusing portions of this software using CBD becomes difficult. Reengineering and maintenance research contains a plethora of software analysis and restructuring techniques that could be used to help us exploit legacy applications for reuse. This thesis focuses on two such techniques and combines variations of them for the purpose of component recovery: A feature location technique called Software Reconnaissance and a design recovery technique called Software Reflexion Modelling. Their combination is called "Component Reconn-exion." We describe the technique, highlight results and evaluation to date and finally discuss further work necessary to complete our contribution as a PhD. thesis.